A STUDY ON THE BOP BUSINESS FOR POVERTY REDUCTION IN DEVELOPING COUNTRIES - MASATOSHI, HARA (Digital Repository of Theses - SSBM Geneva, 2021)
Alleviating poverty has long been discussed as one of the most significant social issues, especially in the developing world. One major problem in addressing the poverty issue is directly linked not merely to fewer job opportunities and an unstable income, but also to poor health, lack of education, inadequate living standards, lack of income, disempowerment, poor, quality of work, and threat of violence. The Base of Pyramid (BOP) business is referred to as a behavior-oriented model or an approach that helps business organizations sufficiently promote their activities in undeveloped and unserved markets. Promoting the BOP business has, therefore, become one of the most innovative ways to mitigate the poverty, primarily by private sectors. However, little previous research has been conducted on the influence of the BOP business opportunities on the poverty reduction and on the BOP business development strategy in connection with the barrier issue of lacking the appropriate economic development conditions. Tran’s economic development stage model and Vernon’s BOP business development model were applied to examine the predictive relationships between poverty reduction and the BOP business maturity. Using secondary data compiled between 2000 and 2020 primarily from the World Development Indicators, the World Governance Indicator, the Human Development Index, and multiple linear regression modeling, the strength of the BOP business cases predicting the percentage change in R2 variance in the poverty headcount ratio was evaluated in the randomly selected 61 economies. Using natural data, the BOP business was found to be a significant predictor (F [1, 1268] = 12.822, p = .000) for poverty headcount ratio, and is thus a major factor in alleviating poverty. Also, employing the grounded theory, through the open, axial, and selective-coding process, developed a conceptual framework of the BOP business development strategy for poverty reduction that combines the economic development conditions per income stage with the BOP business development. Positive social change emanates through continued policy support of the BOP business as a means to mitigate poverty by formulating the framework and its strategy.